Invited commentaryPrognostic value of QRS duration and ejection fraction: going back to the roots - De Luca, Leonardo; Parissis, John; Filippatos, Gerasimos S. (Archives of Medical Science, 2008)
Commentary on Incidence of mortality in 1,040 patients with coronary heart disease or hypertensive heart disease with normal and abnormal left ventricular ejection fraction and with normal and abnormal QRS duration Hoang M. Lai, Wilbert S. Aronow, Archana Rachdev, Amit Asija, Khanh V. Lai, Jerry George, John A. McClung Arch Med Sci 2008; 4, 2: 140–142